System and method for preparing flexible transparent electrode through nanosecond laser processing and application

The film material is etched and cleaned through the nanosecond laser processing system, which solves the problem of high cost of preparing copper films by existing femtosecond lasers, and realizes the low-cost preparation of flexible transparent electrodes, with high conductivity and mechanical flexibility.

CN119730676AActive Publication Date: 2025-03-28SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY +1

Patent Information

Application Number
CN202411601620.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-28
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing method of preparing copper films using femtosecond lasers has the problem of high equipment requirements and high cost, and it is difficult to meet the low cost requirements of industrial electrode preparation.

Method used

A nanosecond laser processing system is adopted, including a laser emission module, a galvanometer polarization module, a water bath cooling module and an ultrasonic module. A nanosecond laser beam is emitted through the laser emission module, and the film material is etched after deflection by the galvanometer polarization module. Combined with water bath cooling and ultrasonic cleaning, flexible transparent electrodes are prepared.

Benefits of technology

The requirements for equipment are reduced and production costs are significantly reduced. At the same time, the flexible transparent electrodes prepared have high conductivity, high light transmittance and excellent mechanical flexibility, which are suitable for large-scale popularization and quantitative production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730676A_ABST
    Figure CN119730676A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of micro-nano machining, in particular to a system and method for preparing a flexible transparent electrode through nanosecond laser machining and application. The galvanometer polarization module is used for deflecting the nanosecond laser beam; the water bath cooling module is used for placing a membrane material, one side of the membrane material is in contact with water in the water bath cooling module, and the other side of the membrane material is etched by the deflected nanosecond laser beam; and the ultrasonic module is used for carrying out ultrasonic cleaning on the etched membrane material. The flexible transparent latticed electrode is prepared in a mode of combining laser emission module etching, galvanometer polarization, water bath cooling and final ultrasonic deburring, and the transparent latticed electrode has the characteristics of high conductivity, high light transmittance, excellent mechanical flexibility and the like; the requirement on equipment is reduced; and the production and manufacturing cost is greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of micro-nano processing technology, and in particular to a system, method and application for preparing a flexible transparent electrode by nanosecond laser processing. Background Art

[0002] As a new type of renewable energy technology, organic solar cells have the advantages of being lightweight, flexible, and relatively low in cost, and have broad application prospects. In organic solar cells, transparent electrodes are an important component, and indium tin oxide (ITO) is usually used as the transparent electrode material. However, indium tin oxide also has some disadvantages, mainly including scarce resources and high costs. Indium is a rare metal and is expensive; ITO film is brittle and easily breaks when bent or hit, which limits its application in flexible electronic devices; and the processing of indium has certain hazards to the human body and the environment.

[0003] The most cost-effective technology currently available is to deposit a copper film on a flexible substrate using a magnetron sputtering system to obtain a flexible copper film; then, at room temperature, a femtosecond laser is used to ablate the flexible copper film, and the moving speed of the electric translation stage is controlled by a computer-aided design system to ensure that the laser-ablated copper film after processing has a suitable surface density, thereby achieving the characteristics of both transmittance and conductivity of the metal film. However, this method still has the following disadvantages: the film used is a self-magnetron sputtered copper film, and the preparation cost of the copper film is relatively expensive compared to other cheaper metal materials; the femtosecond laser, with its extremely short pulse time and high peak power, is not suitable for the low-cost requirements of industrial electrode preparation due to its high equipment technology requirements and high price; in addition, when processing electrodes, laser etching can reach hundreds of meters per second, and because the processing accuracy is at the micron scale, higher requirements are placed on the accuracy and response speed of the three-axis displacement platform, further increasing the production cost.

[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a system, method and application for preparing flexible transparent electrodes by nanosecond laser processing, aiming to solve the problems of high equipment requirements and high costs in the existing use of femtosecond lasers to prepare copper thin films.

[0006] The technical solution of the present invention is as follows:

[0007] A system for preparing a flexible transparent electrode by nanosecond laser processing, comprising:

[0008] A laser emission module, used for emitting a nanosecond laser beam;

[0009] A galvanometer polarization module, used for deflecting the nanosecond laser beam;

[0010] A water bath cooling module is used to place a membrane material, and one side of the membrane material is in contact with water in the water bath cooling module, and the other side is etched by a deflected nanosecond laser beam;

[0011] The ultrasonic module is used to ultrasonically clean the film material after etching.

[0012] The system for preparing flexible transparent electrodes by nanosecond laser processing, wherein the laser emission module includes one of an infrared marking machine and an ultraviolet marking machine.

[0013] The system for preparing flexible transparent electrodes by nanosecond laser processing, wherein the galvanometer polarization module includes an attenuation plate, a power meter, a reflector and a galvanometer; the nanosecond laser beam passes through the attenuation plate, the power meter, the reflector and the galvanometer in sequence.

[0014] The system for preparing flexible transparent electrodes by nanosecond laser processing, wherein the water bath cooling module includes a liquid storage tank with an opening on one side, and a pressing plate with an opening for pressing the film material; the film material is placed on the open side of the liquid storage tank.

[0015] The system for preparing flexible transparent electrodes by nanosecond laser processing, wherein the system for preparing flexible transparent electrodes by nanosecond laser processing also includes a leveling module for adjusting the surface of the film material to keep it level; the water bath cooling module is arranged on the leveling module.

[0016] The system for preparing flexible transparent electrodes by nanosecond laser processing, wherein the system for preparing flexible transparent electrodes by nanosecond laser processing also includes a control module, and the control module is electrically connected to the laser emission module and the galvanometer polarization module respectively, and is used to transmit electrical signals to the laser emission module and the galvanometer polarization module.

[0017] The system for preparing flexible transparent electrodes by nanosecond laser processing, wherein the film material includes a substrate and a metal film deposited on one side of the substrate; the metal film is in contact with water in the water bath cooling module; and / or the material of the metal film is selected from one of aluminum, copper, platinum, and silver.

[0018] A method for preparing a flexible transparent electrode by nanosecond laser processing, comprising the steps of:

[0019] Place the film material on the water bath cooling module and adjust the laser parameters of the laser emission module;

[0020] The laser emission module is used to emit a nanosecond laser beam, and the galvanometer polarization module is used to deflect the laser beam to perform laser ablation on the film material to obtain a printed electrode;

[0021] The printed electrode is ultrasonically cleaned to obtain a flexible transparent electrode.

[0022] The method for preparing a flexible transparent electrode by nanosecond laser processing, wherein the laser parameters include laser processing speed, laser power, laser frequency, Q pulse width, light-on delay, light-off delay, end delay and corner delay;

[0023] Wherein, the laser processing speed is 300mm / s-1000mm / s, the laser power is 0.1W-0.5W, the laser frequency is 50KHz-200KHz, and the Q pulse width is 10ns-30ns.

[0024] A system for preparing flexible transparent electrodes by nanosecond laser processing is used in the preparation of flexible organic solar cells.

[0025] Beneficial effects: The present invention provides a system, method and application for preparing flexible transparent electrodes by nanosecond laser processing. The system for preparing flexible transparent electrodes by nanosecond laser processing includes: a laser emission module for emitting a nanosecond laser beam; a galvanometer polarization module for deflecting the nanosecond laser beam; a water bath cooling module for placing a film material, and one side of the film material is in contact with the water in the water bath cooling module, and the other side is etched by the deflected nanosecond laser beam; an ultrasonic module for ultrasonically cleaning the etched film material. The present invention provides a system for preparing flexible transparent electrodes by nanosecond laser processing composed of a laser emission module, a galvanometer polarization module, a water bath cooling module and an ultrasonic module. A flexible transparent grid electrode is prepared by combining etching with a laser emission module, galvanometer polarization, water bath cooling, and finally ultrasonic burr removal. The transparent grid electrode has the characteristics of high conductivity, high transmittance and excellent mechanical flexibility, and reduces the requirements for equipment and greatly reduces the production cost. Moreover, in the organic flexible solar cell, the flexible transparent electrode can serve as a low-cost flexible substrate and also act as an electrode, and has the advantages of low cost, high light transmittance, low square resistance, light weight, and no cracking when bent to a large extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A schematic diagram of the structure of a system for preparing a flexible transparent electrode by nanosecond laser processing according to the present invention;

[0027] Figure 2 A schematic diagram of the partial structure of a system for preparing a flexible transparent electrode by nanosecond laser processing according to the present invention;

[0028] Figure 3 This is the principle diagram of laser bombardment;

[0029] Figure 4 It is a schematic diagram of the structure of the membrane material;

[0030] Figure 5 Schematic diagram of the aluminum film structure in Example 1;

[0031] Figure 6 This is the light absorption curve of common metal materials in different bands;

[0032] Figure 7 Schematic diagram of different paths and effects in Example 1;

[0033] Figure 8 This is a white light interferometer morphology characterization diagram of the aluminum film electrode in Example 2 without ultrasonic treatment;

[0034] Fig. 9 This is a white light interferometer morphology characterization diagram of the aluminum film electrode after ultrasonic treatment in Example 2;

[0035] Fig.10 The AFM aluminum film line thickness scanning diagram of the aluminum film electrode before and after ultrasonic treatment in Example 2;

[0036] Fig.11 This is a SEM comparison of the aluminum film electrode before and after ultrasound in Example 2;

[0037] Fig.12 This is the effect diagram of the aluminum film electrode in Example 2;

[0038] Fig.13 This is a transmittance measurement data diagram of the aluminum film electrode in Example 2;

[0039] Fig.14 is a schematic diagram of the structure of a flexible organic solar cell device in Example 2;

[0040] Fig.15 This is a CV curve diagram of the flexible organic solar cell device in Example 2 before calibration. DETAILED DESCRIPTION

[0041] The present invention provides a system, method and application for preparing a flexible transparent electrode by nanosecond laser processing. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0042] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.

[0043] like Figure 1 and Figure 2 As shown, the present invention provides a system for preparing a flexible transparent electrode by nanosecond laser processing, comprising:

[0044] A laser emission module 10, used for emitting a nanosecond laser beam;

[0045] A galvanometer polarization module, used for deflecting the nanosecond laser beam;

[0046] The water bath cooling module 20 is used to place the film material 30, and one side of the film material is in contact with the water in the water bath cooling module, and the other side is etched by the deflected nanosecond laser beam;

[0047] The ultrasonic module is used to ultrasonically clean the film material after etching.

[0048] In this embodiment, a system for preparing a flexible transparent electrode by nanosecond laser processing composed of a laser emission module, a galvanometer polarization module, a water bath cooling module and an ultrasonic module is provided. A flexible transparent grid electrode is prepared by a combination of laser emission module etching, galvanometer polarization, water bath cooling, and finally ultrasonic burr removal. The transparent grid electrode has the characteristics of high conductivity, high transmittance, and excellent mechanical flexibility, and reduces the requirements for equipment and greatly reduces the production cost. In addition, in the organic flexible solar cell, the flexible transparent electrode can serve as a low-cost flexible substrate and an electrode at the same time, and has the advantages of low cost, high transmittance, low square resistance, thinness, and no cracking when bent to a large extent.

[0049] Specifically, the present invention uses the system to process the film material with nanosecond laser. Since the duration of the nanosecond laser processing pulse is usually between 1-100ns, this pulse time is long enough so that there will be significant heat accumulation in the process of interaction between the laser and the material. After the material absorbs the laser energy, it will have a long time to produce a thermal effect, causing the temperature of the material surface and its surrounding areas to rise. Then, the high energy of the laser is used to instantly vaporize or ablate the metal film in the film material, and the metal material in these areas is removed to obtain a flexible transparent grid-like electrode, and the flexible transparent grid-like electrode has the characteristics of high conductor performance, high light transmittance and excellent mechanical flexibility. At the same time, the use of this system to prepare flexible transparent electrodes has the advantages of low cost and low equipment requirements, and is suitable for large-scale popularization and quantitative production.

[0050] In some embodiments, the laser emission module includes one of an infrared marking machine and an ultraviolet marking machine.

[0051] Specifically, an infrared marking machine can emit nanosecond lasers to complete the etching of film materials; at the same time, the laser used is not limited to pulse lasers and infrared lasers, and other high-energy lasers can also be used to meet the processing needs of the occasion; if ultraviolet marking equipment is used, patterned grid processing can be performed on materials with ultraviolet absorption, such as transparent glass.

[0052] In some embodiments, the galvanometer polarization module includes an attenuation plate 41, a power meter 42, a reflector 43, and a galvanometer 44; the nanosecond laser beam sequentially passes through the attenuation plate 41, the power meter 42, the reflector 43, and the galvanometer 44. The nanosecond laser beam emitted by the laser emission module is sequentially weakened, the power is measured, and the reflection is made to the galvanometer by the attenuation plate, the power meter, and the reflector, and the nanosecond laser beam is deflected by the response of the galvanometer, so that laser ablation is performed along the route designed on the computer; in this process, the position of the film material remains stationary, thereby solving the focusing problem caused by high-speed movement during processing.

[0053] Since the high energy of the laser will also cause thermal deformation on the surface of the film material, this deformation is very disadvantageous in the tight processing of the laser, and it is easy to cause grid dislocation or focus misalignment. Therefore, in some embodiments, the water bath cooling module 20 includes a liquid storage tank 21 with an opening on one side, and a pressure plate 22 with an opening for pressing the film material 30; the film material 30 is placed on the open side of the liquid storage tank 21. The water bath cooling module can alleviate the thermal deformation of the film material processing and improve the focus and leveling problem. The opening at the upper end of the liquid storage tank facilitates the liquid surface in the liquid storage tank to contact the film material, and the opening of the pressure plate facilitates the laser bombardment on the surface of the film material, and plays a role in fixing the film material.

[0054] The plane levelness of the film is very important for laser processing. If the film is not flat relative to the laser, it is easy to cause grid defects in the grid processing. The principle diagram of laser bombardment is as follows: Figure 3 As shown; therefore, in some embodiments, as Figure 2 As shown, the system for preparing flexible transparent electrodes by nanosecond laser processing further includes a leveling module 50 for adjusting the surface of the film material to maintain a level; the water bath cooling module is arranged on the leveling module. The leveler of the leveling module can ensure that the surface of the film material remains level.

[0055] Specifically, after debugging the laser parameters, designing the path and aligning the focal length, the membrane material can be processed. First, add deionized water to the liquid storage tank, and then place the membrane material face down on the liquid surface of the liquid storage tank to ensure that the liquid surface submerges one side of the membrane material. The purpose of this is to allow the debris generated by laser bombardment of the membrane material to sink into the water to avoid secondary contamination.

[0056] In some embodiments, the system for preparing a flexible transparent electrode by nanosecond laser processing further includes a control module 60, which is electrically connected to the laser emission module and the galvanometer polarization module, respectively, and is used to transmit electrical signals to the laser emission module and the galvanometer polarization module. The control module is used to control the laser emission module and the galvanometer polarization module, that is, the laser parameters and the ablation path are set in the control module, so that the laser emission module emits a nanosecond laser beam according to the laser parameters and the galvanometer polarization module deflects the nanosecond laser beam according to the ablation path.

[0057] In some embodiments, Figure 4 As shown, the film material 30 includes a substrate 31 and a metal film 32 deposited on one side of the substrate 31; the metal film is in contact with the water in the water bath cooling module; and / or the material of the metal film is selected from one of aluminum, copper, platinum, and silver. This laser processing method is suitable for metal films of different materials. For metal films, in addition to aluminum film metal, it is also applicable to copper, platinum, silver and other materials. As long as the processing route, laser power, pulse width and other parameters are fine-tuned, better processing effects can be achieved. For non-metallic films, patterning processing can also be achieved by using suitable absorbing materials, such as patterning preparation on PEDOT films, or using laser processing to remove the conductive layer and other means.

[0058] In some embodiments, the substrate is a PET film.

[0059] In some embodiments, the film material is composed of a PET layer and an aluminum metal layer deposited on one side of the PET layer; the thickness of the aluminum metal layer is 60-90 nm, and the thickness of the PET layer is 60-80 μm. Experimental verification shows that the system has a good processing effect on the same type of metal materials at different thicknesses. In addition, since the PET material is a transparent material and does not absorb infrared lasers, the system can be used to achieve the grid-like preparation of aluminum films on the substrate.

[0060] In a preferred embodiment, the thickness of the aluminum metal layer is 80 nm, and the thickness of the PET layer is 80 μm.

[0061] In addition, the present invention also provides a method for preparing a flexible transparent electrode by nanosecond laser processing, comprising the steps of:

[0062] Step S10: placing the film material on a water bath cooling module and adjusting the laser parameters of the laser emission module;

[0063] Step S20: using the laser emission module to emit a nanosecond laser beam, and deflecting it through a galvanometer polarization module to perform laser ablation on the film material to obtain a printed electrode;

[0064] Step S30: ultrasonically clean the printed electrode to obtain a flexible transparent electrode.

[0065] In this embodiment, the method of preparing a flexible transparent electrode by nanosecond laser processing has strong robustness, has a good processing effect on metal films, and can increase the transmittance while ensuring a small sheet resistance to prepare a low-cost flexible transparent electrode.

[0066] Specifically, a flexible transparent grid electrode is prepared by combining laser emission module etching, galvanometer polarization, water bath cooling, and finally ultrasonic burr removal. The transparent grid electrode has the characteristics of high conductivity, high transmittance, and excellent mechanical flexibility, and reduces the requirements for equipment and greatly reduces the production cost. In addition, in the organic flexible solar cell, the flexible transparent electrode can serve as a low-cost flexible substrate and an electrode at the same time, and has the advantages of low cost, high transmittance, low square resistance, thinness, and no cracking when bent to a large extent.

[0067] In some embodiments, the laser parameters include laser processing speed, laser power, laser frequency, Q pulse width, on-delay, off-delay, end delay and corner delay; wherein, the laser processing speed is 300mm / s-1000mm / s, the laser power is 0.1W-0.5W, the laser frequency is 50KHz-200KHz, and the Q pulse width is 10ns-30ns.

[0068] Specifically, increasing the laser processing speed will reduce the local laser action time, and the ablation will be weakened. Taking the processing of aluminum film with a thickness of 80bn as an example, the laser processing speed is controlled between 300mm / s-1000mm / s for the best effect; increasing the laser power will increase the peak power density of the laser, thereby expanding the laser ablation range. Since the aluminum film is soft, the laser power is adjusted as low as possible, set to within 5% of the laser power, and the laser power is about 0.1-0.5W; adjusting the frequency and pulse width will affect the laser action time, and then affect the marking quality. During the processing, the optimal parameter range for adjustment is 50-200KHz frequency; Q pulse width is 10-30ns, which ensures that the laser processing has a suitable action time. At the same time, the switch delay, light off delay, end delay and corner delay determine the marking conditions in the start, end and turn process. It will affect the edge position of each independent unit. When processing different patterns, the required light-on delay, light-off delay, end delay and corner delay need to be fine-tuned as needed.

[0069] In some embodiments, the ablation radius is determined by directly marking a line on the substrate and measuring the line width.

[0070] The design of the processing path will directly affect the processing quality of the aluminum film, and will have a great impact on burrs, the regularity of the shape of individual units, and damage to the transparent PET substrate. Since the aluminum electrode is formed by ablation, it is necessary to ensure that the path designed according to the route can cover the area of ​​the grid that needs to be ablated. Specifically, the use of unused processing paths will have a great impact on the local heat-affected zone, processing burrs and transmittance. This embodiment uses a spiral linear path or a concentric circle path to complete the ablation of the film material. Preferably, the concentric circle path is used to complete the ablation of the film material, and the effect is better than the spiral linear path.

[0071] In addition, the present invention also provides an application of a system for preparing flexible transparent electrodes by nanosecond laser processing in preparing flexible organic solar cells.

[0072] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.

[0073] Example 1

[0074] In this embodiment, the aluminum film prepared by magnetron sputtering technology is directly purchased online for processing, such as Figure 5As shown in the figure, it consists of an 80μm thick transparent PET layer and an 80nm thick aluminum film deposited on the transparent PET layer. The price of this aluminum film is 13 yuan / m 2 , further reducing material costs; and Figure 6 The light absorption curves of common metal materials in different bands are shown. The absorption rate of aluminum to sunlight is 10%, which is the lowest among common metal materials. Therefore, from the perspective of being transparent and reflecting incident light to promote secondary absorption, aluminum is the best material.

[0075] In this embodiment, the aluminum film is etched using an infrared marking machine. The laser emission module used in this embodiment is an infrared pulse fiber laser. This fiber laser has the characteristics of independent adjustable frequency, and can maintain a high stable peak power output when the frequency is changed. During the experiment, the infrared laser used in this embodiment has a central band of 1064nm, a pulse width of 200ns, and an adjustable frequency range of 1-600kHz.

[0076] During the processing of this embodiment, the processing speed is set to 800 mm / s, the laser power is 0.2 W, the laser frequency is 90 KHz, the Q pulse width is 13 ns, the light-on delay is -150 μs, the light-off delay is 150 μs, the end delay is 50 μs, and the corner delay is 100 μs. The aluminum film is ablated using different paths to obtain a printed electrode.

[0077] like Figure 7 As shown, in this embodiment, a closed spiral path is used to compare with a concentric circle path. Under the same parameters, the ablation effect of the concentric circle path is obviously better than that of the spiral path.

[0078] Example 2

[0079] Before the printed electrode obtained by concentric circle path ablation in Example 1 is used to make flexible organic solar cells, the problem of metal burrs needs to be solved. Metal burrs are caused by laser bombardment. When the laser pulse is irradiated on the metal film, high temperature will be generated, but because the pulse duration is extremely short, the heat does not have enough time to diffuse to the surrounding area. In this way, a very local heat-affected zone is formed. In the heat-affected zone, the high energy of the laser will cause the metal film to vaporize or ablate instantly, but the material will cause thermal expansion while being ablated, and a section of turned-up metal spurs will be left at the edge of the ablated material. Usually, grinding and polishing are used in industry to remove metal burrs, but the aluminum part of the aluminum film itself is only 80nm thick and is very easy to fall off. In the actual experimental process, this embodiment uses an ultrasonic cleaner to ultrasonically clean the aluminum electrode after laser processing (the solution is deionized water, ultrasonic cleaning is 2h, and the temperature is room temperature) to remove the edge burrs.

[0080] In this embodiment, during the preparation of a 150 μm square grid (line width 10 μm), a white light interferometer was used to observe the processed grid after processing. There were many debris and burrs on it. The white light interferometer morphology characterization diagram is as follows: Figure 8 As shown. Then the processed aluminum film is ultrasonically treated to obtain an aluminum film electrode, and its white light interferometer morphology characterization diagram is shown in Fig. 9 As shown, two hours later, the line width was measured using AFM. Fig.10 As shown, it is an AFM aluminum film line thickness scan. Fig.11 As shown, it can be seen intuitively that the burrs are removed after ultrasound.

[0081] The performance test of the aluminum film electrode was carried out, mainly testing its transmittance and square resistance. The transmittance directly affects the amount of photons absorbed by the active layer of the organic solar cell. High transmittance can help improve its photoelectric conversion efficiency; square resistance is used to measure the conductivity of the reaction material. The better the conductivity, the lower the loss of current during transmission. The effect diagram of the aluminum film electrode prepared in this embodiment is as follows: Fig.12 As shown, the transmittance of the aluminum film electrode is about 80% (as shown in Fig.13 As shown, the transmittance of the aluminum film electrode was measured using an ultraviolet spectrophotometer); its square resistance was measured to be <10 ohms / square. Since the thickness of the aluminum film used in this embodiment is 80nm, its transmittance is relatively low. If the thickness of the aluminum film can be further reduced, the transmittance of the thin film electrode will be further improved.

[0082] By using the aluminum film electrode (Al Film) prepared by this method as the bottom electrode, a flexible organic solar cell device with a specific structure of PET / Al Film / PH1000 / PEDOT:PSS 4083 / D18:Y6 / PNDIT-F3N / Ag was prepared, such as Fig.14 As shown. Al Film and PH1000 are used as transparent anodes to receive holes, PH1000 and PEDOT:PSS 4083 are used as hole transport layers; D18 is used as a donor, and the acceptor is Y6, which together form an active layer, which can be prepared by electrostatic spray printing; PNDIT-F3N is used as an electron transport layer; Ag is used as a cathode to accept electrons. After characterization, the flexible organic solar cell device finally achieved an efficiency of PCE = 11.13%, and the CV curve before calibration is shown in the figure below. Fig.15 The test results of the highest efficiency devices in the same batch are shown in Table 1.

[0083] Table 1

[0084]

[0085] In summary, the present invention provides a system, method and application for preparing flexible transparent electrodes by nanosecond laser processing. The system for preparing flexible transparent electrodes by nanosecond laser processing includes: a laser emission module for emitting a nanosecond laser beam; a galvanometer polarization module for deflecting the nanosecond laser beam; a water bath cooling module for placing a film material, and one side of the film material is in contact with the water in the water bath cooling module, and the other side is etched by the deflected nanosecond laser beam; an ultrasonic module for ultrasonically cleaning the etched film material. The present invention provides a system for preparing flexible transparent electrodes by nanosecond laser processing composed of a laser emission module, a galvanometer polarization module, a water bath cooling module and an ultrasonic module. A flexible transparent grid electrode is prepared by a combination of laser emission module etching, galvanometer polarization, water bath cooling, and finally ultrasonic burr removal. The transparent grid electrode has the characteristics of high conductivity, high transmittance and excellent mechanical flexibility, and reduces the requirements for equipment and greatly reduces the production cost. Moreover, in the organic flexible solar cell, the flexible transparent electrode can serve as a low-cost flexible substrate and also act as an electrode, and has the advantages of low cost, high light transmittance, low square resistance, light weight, and no cracking when bent to a large extent.

[0086] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A system for preparing flexible transparent electrodes by nanosecond laser processing, characterized in that: include: A laser emission module, used for emitting a nanosecond laser beam; A galvanometer polarization module, used for deflecting the nanosecond laser beam; A water bath cooling module is used to place a membrane material, and one side of the membrane material is in contact with water in the water bath cooling module, and the other side is etched by a deflected nanosecond laser beam; The ultrasonic module is used to ultrasonically clean the film material after etching.

2. The system for preparing flexible transparent electrodes by nanosecond laser processing according to claim 1, characterized in that: The laser emission module includes one of an infrared marking machine and an ultraviolet marking machine.

3. The system for preparing flexible transparent electrodes by nanosecond laser processing according to claim 1, characterized in that: The galvanometer polarization module comprises an attenuation plate, a power meter, a reflector and a galvanometer; the nanosecond laser beam passes through the attenuation plate, the power meter, the reflector and the galvanometer in sequence.

4. The system for preparing flexible transparent electrodes by nanosecond laser processing according to claim 1, characterized in that: The water bath cooling module comprises a liquid storage tank with an opening on one side, and a pressing plate for pressing the membrane material and provided with an opening; the membrane material is placed on the open side of the liquid storage tank.

5. The system for preparing flexible transparent electrodes by nanosecond laser processing according to claim 1, characterized in that: The system for preparing flexible transparent electrodes by nanosecond laser processing also includes a leveling module for adjusting the surface of the film material to keep it level; the water bath cooling module is arranged on the leveling module.

6. The system for preparing flexible transparent electrodes by nanosecond laser processing according to claim 1, characterized in that: The system for preparing flexible transparent electrodes by nanosecond laser processing also includes a control module, which is electrically connected to the laser emission module and the galvanometer polarization module respectively, and is used to transmit electrical signals to the laser emission module and the galvanometer polarization module.

7. The system for preparing flexible transparent electrodes by nanosecond laser processing according to claim 1, characterized in that: The film material includes a substrate and a metal film deposited on one side of the substrate; the metal film is in contact with water in the water bath cooling module; and / or the material of the metal film is selected from one of aluminum, copper, platinum and silver.

8. A method for preparing a flexible transparent electrode by nanosecond laser processing, characterized in that: Includes steps: Place the film material on the water bath cooling module and adjust the laser parameters of the laser emission module; The laser emission module is used to emit a nanosecond laser beam, and the galvanometer polarization module is used to deflect the laser beam to perform laser ablation on the film material to obtain a printed electrode; The printed electrode is ultrasonically cleaned to obtain a flexible transparent electrode.

9. The method for preparing a flexible transparent electrode by nanosecond laser processing according to claim 8, characterized in that: The laser parameters include laser processing speed, laser power, laser frequency, Q pulse width, light on delay, light off delay, end delay and corner delay; Wherein, the laser processing speed is 300mm / s-1000mm / s, the laser power is 0.1W-0.5W, the laser frequency is 50KHz-200KHz, and the Q pulse width is 10ns-30ns.

10. Use of the system for preparing flexible transparent electrodes by nanosecond laser processing as claimed in any one of claims 1 to 7 in preparing flexible organic solar cells.

Citation Information

Patent Citations

  • Method for preparing flexible transparent electrode material through femtosecond laser ablation

    CN115922096A

Cited By

  • A method for manufacturing a high-conductivity transparent electrode based on a short-time broadband electromagnetic field

    CN122762390A